GOAL 12 OF THE NATIONAL JUSTICE COUNCIL AIMED AT ENVIRONMENTAL SUSTAINABILITY (CIPEEX, 2023)
THIS PAPER PRESENTS THE 'STATE OF THE ART' SCHEDULED FOR THE PREPARATION OF A MASTER'S THESISMASTER'S DISSERTATION THAT IS BEING DEVELOPED IN THE STRICTO SENSU POSTGRADUATE PROGRAM IN ENVIRONMENTALENVIRONMENTAL SCIENCES AT THE EVANGELICAL UNIVERSITY OF GOIÁS (UNIEVANGÉLICA). THE IMPORTANCE OFTHE IMPORTANCE OF STUDIES FOCUSED ON GOAL 12 OF THE NATIONAL COUNCIL OF JUSTICE, WHICH CALLS FOR ENVIRONMENTALACTIONS THAT CONVERGE TOWARDS ENVIRONMENTAL SUSTAINABILITY. IN ORDER TO SUCCEED, A DEDUCTIVEAPPROACH WAS USED, ENHANCED BY BIBLIOGRAPHIC AND DOCUMENTARY TECHNIQUES, WHICH DEVELOPED IN A DESCRIPTIVE AND EXPLANATORYALLOWED THE RESEARCH TO BE DESCRIPTIVE AND EXPLANATORY NATURE.
Keywords: Brazil; National Council of Justice; Goals; Environmental sustainability